2022
DOI: 10.1111/1750-3841.16175
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics in buckwheat hull extracts and their antioxidant activities on bulk oil and emulsions

Abstract: Buckwheat hulls are discarded as waste, although they have more phenolic compounds than buckwheat groats. The antioxidant activities of buckwheat hull extracts prepared with water, 50% ethanol, and 100% ethanol were investigated in bulk oil, oil-in-water (O/W), and water-in-oil (W/O) emulsions. The relationship between the phenolic compositions of the extracts and their antioxidant activities in the three different lipid systems was also evaluated. Fifty percent ethanol extract had the highest total phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
2
0
0
Order By: Relevance
“…Specifically, the TQ and TPC contents in the UAET‐treated samples were significantly higher than those of the other groups ( P < 0.05), although no significant differences were observed for the other parameters. As per previous studies, TPC has been found to be positively correlated with antioxidant activity 28 . Results in this study were aligned with this notion, as the UAET treatment group with the highest TPC content exhibited the highest antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, the TQ and TPC contents in the UAET‐treated samples were significantly higher than those of the other groups ( P < 0.05), although no significant differences were observed for the other parameters. As per previous studies, TPC has been found to be positively correlated with antioxidant activity 28 . Results in this study were aligned with this notion, as the UAET treatment group with the highest TPC content exhibited the highest antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
“…As per previous studies, TPC has been found to be positively correlated with antioxidant activity. 28 Results in this study were aligned with this notion, as the UAET treatment group with the highest TPC content exhibited the highest antioxidant activity. The UT treatment group was found to have the second-highest TQ and TPC content following UAET treatment, while its TFC content was either similar to or lower than that of the untreated group.…”
Section: Discussionsupporting
confidence: 77%